2023
DOI: 10.1002/eqe.3836
|View full text |Cite
|
Sign up to set email alerts
|

Wall‐diaphragm interactions in seismic response of building systems I: Parametric models and elastic response

Abstract: The objective of this paper is to study the elastic seismic response of simplified building models that include considerations of the vertical lateral force resisting system (walls) and the horizontal lateral force resisting system (floor diaphragms) through parametric study. The assumption of rigid diaphragms is often used in the seismic design of buildings; however, research suggests that the diaphragm may influence the fundamental building period and the seismic building response. In this paper, a simplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 36 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…One way to ensure reduced ductility demands is for the wall and diaphragm periods to be “long.” This generally results in a longer building period, as discussed in Fischer and Schafer 9 . Figure 7 shows the ductility demands in the v‐ and hLFRS in the models with long periods, that is, Tw0.5s${T}_w \ge 0.5s$ for the walls and Td0.4s${T}_d \ge 0.4s$ for the diaphragm.…”
Section: Responsementioning
confidence: 86%
See 4 more Smart Citations
“…One way to ensure reduced ductility demands is for the wall and diaphragm periods to be “long.” This generally results in a longer building period, as discussed in Fischer and Schafer 9 . Figure 7 shows the ductility demands in the v‐ and hLFRS in the models with long periods, that is, Tw0.5s${T}_w \ge 0.5s$ for the walls and Td0.4s${T}_d \ge 0.4s$ for the diaphragm.…”
Section: Responsementioning
confidence: 86%
“…In Fischer and Schafer, 9 it was found that the alternative diaphragm design method can accurately predict the elastic hLFRS forces developed in the models when both walls and diaphragms are stiff, 𝑇 𝑤 < 0.5𝑠 and 𝑇 𝑑 ∕𝑇 𝑤 < 0.5 and in some other instances. However, in the majority of cases, the alternative method is unconservative in its estimate of elastic hLFRS forces.…”
Section: 𝑚 𝑑𝑖 = 𝛼 𝑚 𝑚 𝑖mentioning
confidence: 99%
See 3 more Smart Citations